Is routine pre-entry chest radiograph necessary in a high tuberculosis prevalence country? - Jasper, A (J Postgrad Med, 2020)
CONTEXT: Chest radiographs have been used worldwide as a screening tool before employment and training, by various healthcare and other government and nongovernment institutions. Many studies done in the past have demonstrated a relatively low yield for tuberculosis detection and therefore, the authors have questioned this practice. AIMS: To compare the value of the preadmission/employment chest radiograph in two groups, namely, those who have been previously exposed to a healthcare setting (post-exposure group) and those who have not been exposed (pre-exposure group) and to determine if there is a significant difference in tuberculosis detection between these two groups. SETTINGS AND DESIGN: A retrospective review of the reports of the chest radiographs of all candidates appearing for admission to various undergraduate and postgraduate courses in our institute between 2014 and 2017 was performed. MATERIALS AND METHODS: The various abnormalities detected were recorded and the findings in the two groups were compared. STATISTICAL ANALYSIS USED: Chi-square test was used to compare between two group proportions. RESULTS: Thirty out of 4333 (0.69%) candidates in the pre-exposure group and 53 out of 3379 (1.57%) candidates in the post-exposure group showed abnormalities on chest radiographs involving the lung parenchyma, mediastinum, heart, or pleura. In the pre-exposure group, six (0.14%) were found to have underlying cardiac disease and one (0.02%) had tuberculosis. Among the six candidates in the post-exposure group who underwent further investigations in our institute, five (0.15%) were diagnosed to have tuberculosis. Although there was no statistically significant difference in tuberculosis detection between the groups (P = 0.051), there is a trend towards higher detection of tuberculosis in the post-exposure group. CONCLUSIONS: In a country where the prevalence of tuberculosis is high, the pre-employment chest radiograph may still have a role in detecting tuberculosis in the post-exposure group.